Ahmed glaucoma valve implantation in a case of volatile intraocular pressure and preoperative hypotony - Blake Katsev; Gio Campagna; James C. Liu (American Journal of Ophthalmology Case Reports, 2025)
Purpose: To describe a case of Ahmed glaucoma valve (AGV) implantation in a patient with clinical hypotony. In this instance, the AGV helped to stabilize labile intraocular pressures (IOP) by introducing a new outflow pathway that could buffer against variable aqueous inflow. Observation: Our patient presented with severe mixed mechanism glaucoma in his only seeing eye and had a history of failed prior angle surgeries, filtration surgery, and cyclodestructive procedures. After a recent diode, the patient's IOP was difficult to control and ranged from 2 mmHg on a single topical medication to 28 mmHg with no medications. Preoperatively, the patient had visually significant hypotony (corneal and macular folds) while on one topical agent. An AGV was implanted with subsequent stabilization of IOP and vision after postoperative week 6 without the need for IOP lowering agents. The IOP and vision have maintained stability after greater than 1 year of follow-up. Conclusion and Importance: When the outflow pathways are compromised, any fluctuation in the inflow has a much more dramatic effect on the IOP. In such instances, IOP lowering agents have a very narrow therapeutic window and lead to volatility in IOP. This case demonstrates the potential for tube shunt surgery to reduce the lability of IOP in a patient with volatile IOP control.